Strategi dalam Meningkatkan Spiritual Peserta Didik Generasi Alfa : Sinergitas Guru PAK dan Orang Tua - Briamin Marta Lenta Zega; Riste Tioma Silaen (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
This article explores the importance of synergy between Christian Religious Education (CRE) teachers and parents in enhancing the spirituality of Generation Alpha students. This generation lives amidst rapid digital technological advancements that influence how they think, behave, and develop life values. Spiritual formation for Generation Alpha cannot be carried out separately by schools and homes; instead, it must be built through close collaboration between teachers and parents. This study employs a qualitative approach using literature review methods, analyzing various books, academic journals, and relevant data on the role of CRE teachers, parental involvement, and contextual strategies for faith development. The findings indicate that students’ spirituality can be significantly improved through collaborative approaches involving contextual learning, the use of digital media, life modeling, and effective communication between school and family. The article emphasizes that the synergy between CRE teachers and parents is a relevant and essential strategy to nurture Generation Alpha students with strong faith and character in accordance with the teachings of Christ.